Illuminating the Connection: Breastfeeding, Lactose Intolerance, and Early Life Disease Prevention (British Journal of Multidisciplinary and Advanced Studies, 2025)
Breastfeeding plays a critical role in early-life nutrition, influencing epigenetic mechanisms that shape long-term health outcomes. This research reviews existing literature to explore new connections between quantum biology and human physiology, particularly pertaining to the relationship between breastfeeding, early disease prevention, and lactose intolerance, emphasising the role of light in biological systems and neurological conditions such as motor neuron disease and autism spectrum disorder. By integrating perspectives from nutritional epigenetics, quantum biology, and microbiome research, this study highlights the interconnectedness of biological processes that support infant development and lifelong health.